Utilising waqf for sustainable flood mitigation in Malaysia - Manshor, Nurul Mazrah; Hussin, Rohayati; Mohd Sirat, Nur Irinah (Universiti Teknologi MARA, Kedah, 2025)
Flooding is one of the most severe problems in Malaysia, causing significant loss of lives, properties, and socioeconomies due to extremes of monsoonal rains. In response, scholars are investigating the possibility of using waqf (the Islamic endowment) as a sustainable flood management tool as it can provide long-term local solutions. For centuries, waqf has supported religious, educational, and health institutions. However, in environmental management, its applicability is better known as an alternative to flood mitigation.